The role of FDG PET assessment in patients with advanced breast cancer treated with cyclin-dependent kinase 4/6 inhibitors in the second-line setting - Kubeczko, Marcin; Polakiewicz-Gilowska, Anna; D’Amico, Andrea; Chrabański, Olgierd; Świderska, Katarzyna; Chmielik, Ewa; Blamek, Sławomir; Handkiewicz-Junak, Daria; Jarząb, Michał (Frontiers in Oncology, 2024)
BackgroundCyclin-dependent kinase 4/6 (CDK4/6) inhibitors have demonstrated a survival benefit in the second-line treatment of patients with hormone receptor-positive human epidermal growth factor receptor 2-negative advanced breast cancer. However, identifying prognostic biomarkers remains a challenge. Thus, we aimed to assess the prognostic value of 18F-fluorodeoxyglucose positron emission tomography-computed tomography (FDG-PET-CT) performed before CDK4/6 inhibitors initiation.MethodsThis single-center retrospective analysis comprised patients treated with CDK4/6 inhibitors in the second-line setting between 2018 and 2024, with FDG-PET-CT performed before CDK4/6 inhibitor initiation.ResultsThe study included 39 patients with a median age of 63 years (IQR 50 -71). Among them, 12 had de novo metastatic disease (30.8%), and 13 had oligometastatic disease (33.3%). Treatment distribution was as follows: 15 patients received palbociclib (38%), 19 ribociclib (49%), and five abemaciclib (13%). Most patients received fulvestrant (31 patients, 79%), whereas eight patients (21%) were treated with letrozole. The median progression-free survival (PFS) in all studied patients was 25.8 months. Notably, baseline SUVmax (maximum standardized uptake value) showed statistically and clinically significant differences. Patients in the low SUVmax group had a median PFS of 30.7 months, compared to 13.0 months for those in the high SUVmax group (p = 0.038). The 2-year PFS was 76.2% [95% CI 51.8% - 89.4%] for the low SUVmax group, contrasting with 22.3% [95% CI 4.0% - 49.9%] for the high SUVmax group. High SUVmax, poor performance status, and de novo metastatic disease were independent prognostic factors for PFS.ConclusionsFDG-PET-CT performed before cyclin-dependent kinase 4/6 inhibitor commencement is a valuable prognostic tool in hormone receptor-positive human epidermal growth factor receptor 2-negative advanced breast cancer. Patients with SUVmax less than 8.4 experienced extended progression-free survival compared to those with higher SUVmax.